En exklusiv vågbrytare mot den positiva integrationens svallvågor? – En studie av direktiv 2009/81/EG:s påverkan på tillämpningen av artikel 346(1)a FEUF - Andersson,Pontus (2021)
The European Community in the fields of defence and security is at large moving further and further from transnational cooperation towards federal integration. In line with this development, a number of new security policy challenges have today been identified at EU level and both the EU and a majority of its member states agree that they need to be addressed jointly. Nevertheless, demands from member states regarding increased national independence in security matters still exist. Where the objectives of the member states and the ones of the EU therefore possibly won’t coincide, potential conflicts between regulatory will and regulatory power emerges. This is due to the fact that when it comes to legal areas concerning security issues the EU has been conferred relatively few competences to adopt legal instruments. Be that as it may, this hurdle has earlier been noted to be avoided since legislation adopted in fields where the Union possesses more competences can indirectly affect areas more strongly tied to national sovereignty. Taking off from these fundamentals of potential conflict this thesis examines in what ways regulatory instruments, with a legal base of treaty articles relating to the Internal Market, can affect what possibilities the member states have to exercise their exclusive competences linked to national security. This is done by examining the Defence Procurement Directive (dir. 2009/81/EC) and what consequences the instrument has had for the member states’ abilities to safeguard essential security of information interests by applying the treaty derogation of Article 346(1)a TFEU. The thesis surveys the legal development of the article by firstly examining it’s legal position before the Defence Procurement Directive, secondly by shedding light on provisions in the directive of relevance to the article, and lastly by looking into Union Law materials, on the legislation, that have been submitted after the directive’s entry into force. When assessing provisions of the directive, the outline mirrors the instrument’s purpose as replacement for article 346(1)a TFEU. Stemming from the article’s ratione materiae, requirements of application, and security of information considerations, the directive is examined with a corresponding sectioning. In light of the results of the examination, the directive’s direct consequences for the scope of article 346(1)a TFEU and it’s effects relating to demands of application for the treaty derogation, asked in case or soft law, are then analyzed. The thesis concludes that in terms of positive integration the Union legislator generally and deliberately act in a giving-and-taking fashion, as well as with caution, when it adopts internal market regulation closely linked to national security concerns – in order not to overstep the boundaries of the member states’ exclusive security competences. At the same time it is also noted that the mere existence of secondary legislation, when interplaying with demands of application from case or soft law, can entail competence-delimiting consequences. Lastly the thesis observes that the above-mentioned caution can sometimes be abandoned in order for the adopted legislation to triumph, and that many conclusions of the thesis would benefit from a greater amount of case law on the Defence Procurement Directive and article 346(1)a TFEU alike.
Keywords: EU-rätt; Statsrätt